Implementasi Metode Peer Teaching (Tutor Sebaya) dalam Mempercepat Pemahaman Literasi Bahasa Arab dan Bahasa Kitab Kuning Santri di Pondok Pesantren Anwarul Huda Malang - Wahyudi Widodo (ARZUSIN, 2026)
Low understanding of Arabic literacy and kitab kuning among santri remains a problem in pesantren learning, particularly because of the dominance of teacher-centered conventional methods that insufficiently encourage santri active participation. This study aims to analyze the implementation of the peer teaching or peer tutoring method in accelerating santri understanding of Arabic literacy and kitab kuning at Pondok Pesantren Anwarul Huda Malang. This study used a qualitative approach with a descriptive research type. The research subjects included santri, peer tutors, and ustadz. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results showed that the peer teaching method was effective in improving santri understanding of Arabic literacy and kitab kuning. This method created a more active, communicative, and collaborative learning atmosphere, enabling santri to understand the material more easily through explanations from peer tutors. Improvement was also evident in the ability to read kitab gundul, understand nahwu and sharaf, and translate texts. In addition, this method had a positive impact on santri self-confidence and learning motivation, although it still faced challenges in the form of differences in tutor quality and limited implementation time. These findings confirm that peer teaching can serve as a relevant alternative learning strategy to strengthen Arabic literacy and kitab kuning in the pesantren environment.